EDBEHOS Sleep Therapy on Sleep Quality in Children with Acute Lymphoblastic Leukemia During Chemotherapy - Andrye Fernandes; Yessi Andriani (Jurnal Keperawatan Silampari, 2024)
This study aims to analyze the optimization of meeting children's rest/sleep needs by implementing EdBeHos Sleep Therapy. The method used is quasi-experimental with the application of Evidence-Based Nursing Practice EdBeHos Sleep Therapy. The study's results found a significant difference in sleep quality scores between the intervention and control groups (p<0.001). In conclusion, the EdBeHos Sleep Therapy intervention can be applied to overcome sleep problems so that it can improve the quality of life of children with cancer. Keywords: Edhebos, Sleep Quality, Acute Lymphoblastic Leukemia, Chemotherapy, Sleep Quality